Containment of Phytoplasma-Associated Plant Diseases by Antibiotics and Other Antimicrobial Molecules - Assunta Bertaccini (MDPI AG, 2021)
Phytoplasmas are plant-pathogenic bacteria that infect many important crops and environmentally relevant plant species, causing serious economic and environmental losses worldwide. These bacteria, lacking a cell wall, are sensitive to antibiotics such as tetracyclines that affect protein synthesis mechanisms. Phytoplasma cultivation in axenic media has not been achieved for many strains; thus, the screening of antimicrobials must be performed using mainly in vivo materials. Some studies have investigated using in vitro phytoplasma-infected shoots, and several antimicrobials, including tetracyclines, have been tested. The screening of phytoplasma antimicrobials is important for the sustainable control of phytoplasma-associated diseases. The use of molecules with different modes of action such as ribosome inactivating proteins, plant hormones, and resistance inducers such as plasma-activated water, is advised, to avoid the use of antibiotics in agriculture and the possible emergence of resistant microbial strains.